Hepatic glutamine synthetase augmentation enhances ammonia detoxification. Issue 6 (11th March 2019) - Soria, Leandro R.; Nitzahn, Matthew; De Angelis, Angela; Khoja, Suhail; Attanasio, Sergio; Annunziata, Patrizia; Palmer, Donna J.; Ng, Philip; Lipshutz, Gerald S.; Brunetti‐Pierri, Nicola
Abstract: The urea cycle and glutamine synthetase (GS) are the two main pathways for waste nitrogen removal and their deficiency results in hyperammonemia. Here, we investigated the efficacy of liver‐specific GS overexpression for therapy of hyperammonemia. To achieve hepatic GS overexpression, we generated a helper‐dependent adenoviral (HDAd) vector expressing the murine GS under the control of a liver‐specific expression cassette (HDAd‐GS). Compared to mice injected with a control vector expressing an unrelated reporter gene (HDAd‐alpha‐fetoprotein), wild‐type mice with increased hepatic GS showed reduced blood ammonia levels and a concomitant increase of blood glutamine after intraperitoneal injections of ammonium chloride, whereas blood urea was unaffected. Moreover, injection of HDAd‐GS reduced blood ammonia levels at baseline and protected against acute hyperammonemia following ammonia challenge in a mouse model with conditional hepatic deficiency of carbamoyl phosphate synthetase 1 ( Cps1 ), the initial and rate‐limiting step of ureagenesis. In summary, we found that upregulation of hepatic GS reduced hyperammonemia in wild‐type and Cps1 ‐deficient mice, thus confirming a key role of GS in ammonia detoxification. These results suggest that hepatic GS augmentation therapy has potential for treatment of both primary and secondary forms of hyperammonemia.